From diagnosis to rehabilitation of trigger finger: a narrative review - Donati, Danilo; Ricci, Vincenzo; Boccolari, Paolo; Origlio, Flavio; Vita, Fabio; Naňka, Ondřej; Catani, Fabio; Tarallo, Luigi (BMC musculoskeletal disorders, 2024)
Trigger finger (TF), also known as stenosing flexor tenosynovitis, is a common pathology of the fingers causing functional deficit of the hand. In recent years, new therapeutic approaches such as extracorporeal shock wave therapy (ESWT) and ultrasound-guided (USG) procedures have joined the most traditional conservative treatments as the adaptation of daily activities involving the affected hand and the orthosis. Likewise, the ultrasound (US) examination of the affected finger using modern high-frequency probes has progressively become part of the comprehensive assessment of patients with TF coupled with the medical history, the physical examination, and the functional scales. In this sense, considering the technological advances in both diagnostic and therapeutic fields, the non-surgical strategies have progressively grown defining a rehabilitation panel more complex than in the past. The present manuscript aims to provide an updated practical guide for clinicians and surgeons reviewing the state-of-art of both the assessment and the treatments of patients with TF to plan tailored rehabilitation management taking advantage of the matching of traditional and novel techniques.
Keywords: Rehabilitation; intervenční ultrasonografie; Trigger; Ultrasonography, Interventional; lidé; Extracorporeal Shockwave Therapy; Management; léčba mimotělní rázovou vlnou; Treatment; lupavý prst; Treatment Outcome; Trigger Finger Disorder; výsledek terapie; Finger; Conservative; Humans